KSU lean gain assessment program - G L Keeler; Michael D Tokach; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1991)
KSU Lean Gain Assessment is a new program developed at Kansas State University to allow producers to assess the actual lean gain of their pigs under normal farm conditions. The procedure is inexpensive and relatively simple and provides information that will assist producers in monitoring their genetic progress. Additionally, farm-specific diets can be formulated to match nutrient levels with the actual genetic potential of pigs on an individual farm.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Genetics; Nutrition; Lean gain